Influence of the sample area in the variability of losses in the mechanical harvesting of soybeans - Loureiro Júnior, Antônio M.; Silva, Rouverson P. Da [UNESP]; Cassia, Marcelo T. [UNESP]; Compagnon, Ariel M. [UNESP]; Voltarelli, Murilo A. [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2014)
The mechanical harvesting is an important stage in the production process of soybeans and, in this process; the loss of a significant number of grains is common. Despite the existence of mechanisms to monitor these losses, it is still essential to use sampling methods to quantify them. Assuming that the size of the sample area affects the reliability and variability between samples in quantifying losses, this paper aimed to analyze the variability and feasibility of using different sizes of sample area (1, 2 and 3 m²) in quantifying losses in the mechanical harvesting of soybeans. Were sampled 36 sites and the cutting losses, losses by other mechanisms of the combine and total losses were evaluated, as well as the water content in seeds, straw distribution and crop productivity. Data were subjected to statistical analysis (descriptive statistics and analysis of variance) and Statistical Control Process (SCP). The coefficients of variation were similar for the three frames available. Combine losses showed stable behavior, whereas cutting losses and total losses showed unstable behavior. The frame size did not affect the quantification and variability of losses in the mechanical harvesting of soybeans, thus a frame of 1 m² can be used for determining losses.

A colheita mecanizada é uma fase importante no processo produtivo da soja, sendo comum, neste processo, a perda de quantidade significativa de grãos. Apesar da existência de mecanismos para monitorar essas perdas, ainda é fundamental o uso de métodos de amostragem para a quantificação das mesmas. Pressupondo-se que o tamanho da área amostral afeta a confiabilidade e a variabilidade entre as amostras na quantificação das perdas, este trabalho teve como objetivo analisar a variabilidade e a viabilidade do uso de diferentes tamanhos de área amostral (1, 2 e 3 m²) na quantificação de perdas na colheita mecanizada de soja. Foram amostrados 36 pontos e avaliadas as perdas provocadas pelo corte das plantas, pelos demais mecanismos da colhedora e totais, o teor de água das sementes, a distribuição de palha e a produtividade da lavoura. Os dados foram submetidos à análise estatística (estatística descritiva e análise de variância) e ao Controle Estatístico de Processo (CEP). Os coeficientes de variação foram semelhantes para as três armações avaliadas. As perdas na máquina apresentaram comportamento estável, enquanto as perdas no corte das plantas e totais apresentaram comportamento instável. O tamanho da armação não interferiu na quantificação e na variabilidade das perdas na colheita mecanizada de soja, podendo ser usada armação de 1 m² para a determinação das perdas.
Influência da área amostral na variabilidade das perdas na colheita mecanizada de soja
Keywords: Statistical Process Control (SPC); control charts; Combine; Controle Estatístico de Processo (CEP); cartas de controle; colhedora